A Proposed Study on the Transplacental Transport of Parabens in the Human Placental Perfusion Model. Issue 6 (December 2013) - Mathiesen, Line; Zuri, Giuseppina; Andersen, Maria H.; Knudsen, Lisbeth E.
Human exposure to parabens as a preservative used in personal care products is of increasing concern, as there is evidence from in vivo and in vitro studies of hormone disruption in association with exposure to parabens. Transport across the placenta could be critical for risk assessment, but the available data are sparse. The aim is to develop a method for estimating fetal exposure, via the placenta, to the most commonly-used parabens, by using a human placental perfusion model. The use of human tissue is vital for determining human fetal exposure, because animal studies are of little relevance, since the placenta exhibits significant interspecies variation. An HPLC model is currently being established to simultaneously quantify four different parabens, namely, methylparaben, ethylparaben, propylparaben and butylparaben, and their main metabolite, p -hydroxybenzoic acid. With this model, we aim to determine the transport kinetics of these parabens across the human placenta, and to investigate placental metabolism, including differences in transport due to molecular characteristics. This will facilitate assessment of the risks associated with the use of paraben-containing products during pregnancy.